(untitled) (Journal of the College of Basic Education, 2026)
The goal of the English as a second language course book is to increase students’ awareness of the value of language use for more than just communication. It also intends to expand their understanding of the diverse cultures throughout the world, including their customs, social customs, and religious beliefs. Accordingly, this paper aims at presenting a general understanding of how learners encounter with other cultures which is the most important factor for successful communication with other cultures and to show how certain texts are important for developing learners’ critical culture awareness of other cultures. That is, through interact with their people to develop both intercultural and linguistic competence of learners. This study concludes that learning culture is an essential part of an ELT syllabus. Moreover, it shows us that centre’s cultural materials are detrimental to the cultures of the periphery countries. Classroom activities can enable the learners to expand their linguistic abilities, become language users that are more competent and develop appropriate attitudes vital for intercultural communication exchanges that are efficient.